Soil nutrient effect on microbial diversity and community composition is modulated by soil aggregate fractions in Yuanjiang savanna, China - Jinxiu Zhang; Zihao Guo; Can Wang; Na Lin; Chunyu Hou; Yajun Chen; Meiyan Zhang; Jianping Wu (Applied Soil Ecology, 2026)

RCTUnet: a deep learning model for crop-residue-soil image segmentation and crop residue cover extraction - Ting Li; Yang Liu; Haikuan Feng; Meiyan Shu; Hao Yang; Yuanyuan Fu; Xin Xu; Yinghao Lin; Hongbo Qiao; Wei Guo; Xinming Ma; Lei Shi; et al. (Journal of Zhejiang University-SCIENCE B, 2026)

Redox-pathway steering enables photocatalytic valorization of CO2 and 1-phenylethanol with record quantum efficiency - Xinyu Xu; Jia Zhou; Meiyan Guo; Wanxiang Yang; Bo Su; Meifang Zheng; Xiahui Lin; Xue Feng Lu; Yidong Hou; Guigang Zhang; Wei Lin; Sibo Wang (Science Bulletin, 2026)

Comparison of growth performance and non‐specific immunity of Nile tilapia ( Oreochromis niloticus ) fed with non‐germinated and germinated faba bean - Xi Xie; Meiyan Chen; Qingqing Li; Ling Yang; Zhendong Qin; Lijuan Zhao; Shaowen Liang; Li Lin (Journal of Fish Biology, 2025)
Faba bean ( Vicia faba L.) has garnered interest from the aquatic feed industry as a plant‐based ingredient that may enhance muscle hardness and crispness in tilapia. However, faba beans contain numerous anti‐nutritional factors (ANFs) that could affect animal growth and health through their metabolic products. Germination effectively reduces the content of ANFs in faba beans; however, the effects of germinated faba beans on tilapia growth and non‐specific immunity remain unclear. In this study, the growth parameters, antioxidant activity, carbon metabolic enzyme activity and immune‐related gene expression profiles of tilapia fed with germinated faba beans (FB1 and FB5 groups) and non‐germinated faba beans (FB0 group) were compared. The FB1 and FB5 groups exhibited heavier body weight (514.39 ± 111.66 g and 546.87 ± 98.16 g) compared to the FB0 group (392.53 ± 78.34 g) on day 80 ( p interleukin‐1 beta ( IL‐1β ), C‐C motif chemokine ligand 3 ( CCL3 ) and tumour necrosis factor‐alpha ( TNF‐α ) were downregulated initially and then gradually upregulated by day 80. Expression of heat shock protein 70 ( Hsp70 ) upregulated in the FB1 and FB5 groups relative to that in normal tilapia (control). These findings suggest that incorporating faba beans into tilapia feed may reduce oxidative stress and modulate immune responses in tilapia cultures.

Early Pleistocene integration of the Yellow River III: Paleontological and paleohydrological evidence from the Fenwei Basin - Guoqiao Xiao; Xinru Lin; Tianran Chen; Qing Pan; Hong Ao; Yange Wang; Meiyan Liang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Mechanism of earthworm coelomic fluid inhibits multidrug-resistant bacteria and blocks resistance transmission - Lihan Lin; Jingwen Luo; Zhan Li; Hongan Guo; Tao Liu; Xiaojie Sun; Meiyan Xing (Environmental Pollution, 2025)

Network pharmacology, bioinformatics analysis, and experimental validation to reveal the target and pharmacological mechanism of DHDK in treating breast cancer - Lin Meng; Xinyue Wang; Fangyu Zhang; Meiyan Zhang; Yuqing Wang; Dingjia Guo; Jing Hong; Yunli Zhao (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Conformational control of Ni coordination sites in pyridyl-functionalized covalent organic frameworks for exceptional CO2 photoreduction - Xinyi Zeng; Meiyan Guo; Lei Wang; Hetao Xu; Chao Lin; Zhipeng Luo; Fengtao Zhang; Shipeng Zhu; Sibo Wang; Yuanxing Fang; Wei Lin; Xiong Chen (Science Bulletin, 2025)

A robust Bayesian Multi-Machine learning ensemble framework for probabilistic groundwater level forecasting - Feilin Zhu; Yimeng Sun; Mingyu Han; Tiantian Hou; Yurou Zeng; Meiyan Lin; Yaqin Wang; Ping-an Zhong (Journal of Hydrology, 2025)

Quantitative evaluation of the impact of hydrological forecasting uncertainty on reservoir real-time optimal operation - Feilin Zhu; Yaqin Wang; Bojun Liu; Qing Cao; Mingyu Han; Yurou Zeng; Meiyan Lin; Lingqi Zhao; Xinrong Wang; Zhiqi Wan; Ping-an Zhong (Stochastic Environmental Research and Risk Assessment, 2024)

Mutation of OsNRAMP5 reduces cadmium xylem and phloem transport in rice plants and its physiological mechanism - Wanyue Zhang; Meiyan Guan; Mingxue Chen; Xiaoyan Lin; Ping Xu; Zhenzhen Cao (Environmental Pollution, 2024)

Spatial and variety distributions, risk assessment, and prediction model for heavy metals in rice grains in China - Zhenzhen Cao; Meiyan Guan; Xiaoyan Lin; Wanyue Zhang; Ping Xu; Mingxue Chen; Xiaolong Zheng (Environmental Science and Pollution Research, 2023)

Soil pH restricts the ability of biochar to passivate cadmium: A meta-analysis - Beilei Wei; Yunchang Peng; Paramsothy Jeyakumar; Longxin Lin; Dongliang Zhang; Meiyan Yang; Jinning Zhu; Carol Sze Ki Lin; Hailong Wang; Ziting Wang; Chong Li (Environmental Research, 2023)

Sediment and interstitial water heavy metals in mangrove restoration wetland and preliminary exploration of microplastics in interstitial water - Bo Hu; Jiahui Lin; Junming He; Meiyan Zheng; Jinyang Wang; Yiting Nan; Yaqing Wu; Peiyong Guo (CATENA, 2023)

Comparison of growth, and non-specific immune of crisp and ordinary tilapia (Oreochromis niloticus) - Qingqing Li; Yao Huang; Xi Xie; Xiaoqian Zhai; Meiyan Chen; Dejin Liang; Ming Cao; Shaowen Liang; Li Lin (Aquaculture, 2023)

A constant parameter time domain model for dynamic modelling of multi-body system with strong hydrodynamic interactions - Meiyan Zou; Mingsheng Chen; Ling Zhu; Lin Li; Wenhua Zhao (Ocean Engineering, 2023)

Effect of straw biochar from different crops on growth and nutrient uptake by peach (Prunus davidiana) seedlings - Qin Liu; Haoran Zhang; Yan Wang; Jing Sun; Dong Chen; Meiyan Tu; Lijin Lin (Acta Physiologiae Plantarum, 2022)

Bioinformatics analysis and expression of a novel protein ROP48 in Toxoplasma gondii - Jian Zhou; Lin Wang; Aihua Zhou; Gang Lu; Qihang Li; Zhilin Wang; Meiyan Zhu; Huaiyu Zhou; Hua Cong; Shenyi He (Acta Parasitologica, 2016)
is an obligate intracellular apicomplexan parasite, and can infect warmblooded animals and humans all over the world. In the past years, ROP family genes encoding particular proteins of